Segmentasi Perilaku Pembelian Pelanggan Berdasarkan Model RFM dengan Metode K-Means - Siti Monalisa (Query: Journal of Information Systems, 2018)
This study aims to measure customer purchase behavior by using RFM model with K-Means, silhouette Index method. Using historical data by Cendana Perdana Perkasa Distributor to data this study. The company has never to measured customer buy behavior by this model. The results of this study showed that there 3 cluster with 0,589 silhouette Index. Based on the highest silhouette Index then the cluster is divided into 3 segment with some segments 1 is 57 customers, segment 2 is 257 customers and segment 3 is 8 customers. The best purchase value is segment 3 with symbolized byR↓F↑M↑ that means this segment has high frequency and monetary as well as low regency. The segment has potential customers for the future. The worst purchase value is segment 1 withv symbolised byR↑F↓M↓ that means this segment has low-frequency and monetary as well as high regency. The segment has an unclear or uncertain customer will be a potential customer. Keywords: Customer Purchase Behavior, K-Means, RFM and Silhoutte Index